Gendered Social Norms Change in Water Governance Structures Through Community Facilitation: Evaluation of the UPWARD Intervention in Tanzania - Eaton, Jacob; Krishna, Aditi; Sudi, Christina; George, Janeth; Magomba, Christopher; Eckman, Anne; Houck, Frances; Taukobong, Hannah (Frontiers in Sociology, 2021)
Background: In rural Tanzania, women and girls disproportionately bear the burden of water scarcity. Gendered social norms on the acceptability of women’s participation in the public sphere limit their decision-making power within local water governance structures. The UPWARD (Uplifting Women’s Participation in Water-Related Decision-Making) intervention sought to understand how a community-based gendered social norms approach using organized diffusion can lead to changes in the gendered social norms impacting women's participation in water-related governance structures. Methods: As part of WARIDI, a 5-year integrated water resource management (IWRM) program, a gendered-social norms change (GSNC) activity (UPWARD: Uplifting Women’s Participation in Water-Related Decision-Making) was implemented in two villages in Iringa and Kilombero districts. Encouraging organized diffusion, UPWARD promoted gender-equitable norms among a critical mass of community members. WARIDI identified and trained a Community Facilitation Team (CFT) of three women and men to lead a series of education and empowerment sessions in two communities. The intervention reached > 300 individuals directly (~10% of total village population). Changes in social norms were assessed through social norms analysis plots (SNAP) delivered in focus group discussions (FGDs) of 8-12 participants. Results: At baseline, most participants reported that women’s involvement in water-related decision-making was restricted to household decisions. Men viewed themselves as primary decision-makers in water governance. Women who spoke in village meetings experienced sanctions for disrespect and outspokenness; their husbands were teased for being ‘controlled.’ At endline, participants reported fewer instances of ridicule towards women’s participation. Women expressed a greater sense of solidarity with each other; men reported greater respect for men whose wives contribute. The intervention’s effects appeared more pronounced in areas with greater cultural heterogeneity, suggesting norm change may be harder to affect where norms are tighter. Conclusion: UPWARD provides evidence that gendered social norms change programs can have identifiable impacts on women’s participation in water-related decision-making over a short time. While other interventions have used larger, multi-level strategies to affect gender norms, UPWARD has shown that community mobilization with brief (~4 month) but concentrated engagement with communities can promote changes in social norms that persist at least 6 months after intervention’s end.